Comprehensive Review of Health Administration Practices with A Focus on Laboratory Management - ALMUTAIRI, OMRAN ABDULLAH SAAD; ALSAIHAIMI, GHALA RSEED AREAR; ALMUTAIRI, JABER MODKHEL S; ALHARBI, TARIQ EID M; ALANAZI, MUNAYFAH AWAD ABDULAZIZ; ALMUTAIRI, AHMED MATAR OBAIDAN; ALREESHYDE, ASHWAQ A M; ALJOHANI, AMANI ABDULAZIZ AWDAH; ALANAZI, NAWT MAHAL SAUD; ALMUTIRI, HEZAM AWYD M; AL-QARNI, WALEED AYED (Journal of Ecohumanism, 2024)
This paper concludes that effective health administration is vital for overall organizational efficiency, particularly in the healthcare industry, measured through the level of accomplishment of laboratory objectives. Therefore, this extensive literature review aims to discuss the main principles of leadership in health administration with an emphasis on laboratory management, which is the most sensitive and known to be effective, efficient, and innovative. This paper reviews the advancements in management in healthcare facility laboratories, including systems, technology, and guidelines. Particular emphasis is placed on the developments in the field of laboratory management resulting from improvements in health informatics, regulation, and mandatory improvements in the quality and safety of laboratory testing. The review also includes best practices and emerging trends, including staffing, training and development, resources, planning and control, and compliance. Thus, this paper offers a literature review of previous research and new data on factors enhancing laboratory management best practices and the corresponding recommendations.